Student knowledge level: Handling sports injuries using the R.I.C.E method - Hidayatullah, M. Syarif; Fajrin Rahmi, Miftah; Aldino; Raibowo, Septian (Indonesian Journal of Sport, Health and Physical Education Science, 2024)
The purpose of this study was determine the level of student knowledge of handling injuries using R.I.C.E method in the physical education study program FKIP University of Bengkulu. The problem in this study was that it was not yet know hiow high the level of student knowledge about handling sport injuries using the R.I.C.E method in the physical education study program FKIP University of Bengkulu. The type of research was descriptive research with a qualitative approach with survey method. The subject of research was a physical education student of the FKIP University of Bengkulu. Using data collection technique questionnaires, interview and documentation. Data analysis used in this research was data reduction, data display, conclusion/verification. The result of percentage of all aspects in the very high category were 61.39% (54 student) in the high category 39.64% (34 student) thus the data concluded that the level of student knowledge of handling sports injuries with the R.I.C.E method can be concluded that student have a very high level of knowledge